Separation and Identification of Curcuminoids from Asian Turmeric (Curcuma longa L.) Using RP-HPLC and LC-MS - Lee, K.J.; Kim, Y.S.; Ma, J.Y. (Asian Journal of Chemistry, 2012)
In this study, three major curcuminoids in turmeric, including curcumin, demethoxycurcumin and bismethoxycurcumin, were efficiently extracted by optimizing the extraction conditions and were simultaneously identified using a fast and reliable HPLC-UV-MS method and thin layer chromatography. The analysis was performed with a C18 column and the UV wavelengths were fixed at 425 and 254 nm. The total extraction yields of curcumin and demethoxycurcumin increased with the extraction time from 1 to 4 h, but scarcely increased after 4 h. LC-MS following thin layer chromatography analysis provided efficient molecular weight information for the two major curcuminoids in the turmeric extracts.